Pembuatan Herbal Mineral Blok (HMB) Sebagai Suplemen Untuk Meningkatkan Produksi Ternak Ruminansia pada Kelompok Tani Sidomulyo IX, Lampung Timur - Melia Afnida Santi; Desi Maria Sinaga; Heni Suryani; Vindo Rossy Pertiwi; Gusma Gama Maradon; Boby Arya Putra (Institut Pertanian Bogor, 2026)
This Community Service Activity (PKM) aims to enhance the understanding and skills of farmers regarding the importance of feed supplements in meeting the nutritional needs of ruminant livestock. The activity was conducted at the Sidomulyo IX Farmers Group, Labuhan Ratu IX Village, Labuhan Ratu District, East Lampung Regency. The supplement introduced is in the form of a Herbal Mineral Block (HMB), which is a mineral- and herbal-based feed additive to support the health and productivity of ruminant livestock. The main issue for the partners is the still low level of knowledge among farmers regarding the importance of meeting the mineral needs of livestock. Activities were carried out through socialization, discussions, and training in HMB production so that farmers could understand and apply it independently. The evaluation of the activity shows that out of the total 15 participants who attended the training, most were able to understand and apply the HMB production techniques. The pretest results indicated that before the activity, 80% of the participants were in the category of not understanding and having little understanding of the importance of livestock nutrition fulfillment, the benefits of HMB, and its production techniques. After the activity was conducted, the posttest results showed a significant improvement, with 93.3% of the participants falling into the category of understanding and very understanding. Additionally, the participant satisfaction evaluation shows that all participants (100%) found the activity very beneficial; 86.67% of participants stated that the material presented was very clear; 80% of participants were interested in producing HMB independently; and 93.3% of participants were very satisfied with the implementation of the activity. Some participants also suggested ideas to modify the HMB formulation according to the needs of livestock in their respective areas. The results of this activity show that the extension and demonstration of HMB production are effective in increasing the knowledge, skills, and interest of farmers in utilizing herbal and mineral-based feed supplements as an effort to support the sustainable productivity of ruminant livestock.